2022
DOI: 10.1093/her/cyac012
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and mobile application for self-care, self-efficacy and related knowledge

Abstract: Managing hypertension is not only concerned with lowering blood pressure (BP) by using antihypertensive medications but also aims at minimizing its consequences through adopting self-care. The aim of this study was to assess the effectiveness of mobile application on self-care, BP control, self-efficacy and hypertension-related knowledge among adult patients with hypertension. A randomized design, two groups, pretest–posttest, between subjects with a 1:1 allocation ratio was used. The sample was selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…These findings are consistent with Dwairej and Ahmed’s findings that smartphone applications lead to more statistically significant knowledge scores ( p = 0.005), BP control ( p = 0.005), and self-care ( p = 0.04). 40 This review is consistent with previous studies in finding that smartphone applications have unique features that facilitate self-care actions and improve outcomes in HD patients. Kosa et al reported that nutritional mobile applications greatly assist patients in tracking their food intake, recognizing food items, and estimating portions.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with Dwairej and Ahmed’s findings that smartphone applications lead to more statistically significant knowledge scores ( p = 0.005), BP control ( p = 0.005), and self-care ( p = 0.04). 40 This review is consistent with previous studies in finding that smartphone applications have unique features that facilitate self-care actions and improve outcomes in HD patients. Kosa et al reported that nutritional mobile applications greatly assist patients in tracking their food intake, recognizing food items, and estimating portions.…”
Section: Discussionsupporting
confidence: 89%
“…If patients are made aware that self-care tools may aid in illness management and control. Then, it will be simpler for patients to embrace these apps since they would think that by following self-care the applications, their recovery will be substantially accelerated [ 64 , 66 , 67 ]. The team can highlight the advantages of an anxiety and depression self-care app, like better health information access‌ [ 68 ], lower medical errors and treatment costs, improved coordination among healthcare providers, and reduced patient travel [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased knowledge related to ACS symptoms is closely related to the faster ability to recognize the early symptoms of ACS. This will increase awareness regarding ACS symptoms, so there is no need to wait for symptoms to worsen to decide to seek help (3,(7)(8)(9)(10)(18)(19)(20)(21).…”
Section: Early Detection Of Acsmentioning
confidence: 99%
“…Increased knowledge through the DETAK application has shown to increase respondents' self-efficacy in first aid for ACS (19,25). The independent learning experience through the media provided has made respondents feel more confident because they can learn and try to identify themselves regarding the symptoms and risk factors they feel.…”
Section: Early Detection Of Acsmentioning
confidence: 99%